Cognitive Motive of the Kindergarten Child (Journal of the College of Education for Women, 2022)
Encouraging children towards the cognitive motivation through the discovery and knowledge of the environment around them is essential. Thus, during the two researchers’ supervision of the practical lessons that involved the female students’ application of their experience in the Applied Kindergarten Laboratory, it has been noticed that there was a difference in the cognitive motivation of kindergarten children. In order to reinforce the research problem, the two researchers sent an open questionnaire to a sample of randomly selected kindergarten teachers from Al-Karkh and Al-Rasafa sides. The responses collected accentuated the researchers’ sense of the existing problem. To achieve the aim of the study represented by examining the kindergarten child’s cognitive motive, and the differences of the motive in terms of gender variable (male, female), a sample of (150) (males, females) children of an age ranging between (5-6) years of the preliminary stage was selected. The sample was randomly selected from the governmental kindergartens in Baghdad from its two sides Karkh and Rusafa. The two researchers prepared a triple alternatives measure of cognitive motive, which consisted of (45) items divided into two fields. The first field that was concerned with knowing the environment that surrounds the child consisted of (26) items, whereas the second field, which is about problem solving, consisted of (19) items. The results have shown that kindergartens children have a cognitive motive. To achieve the validity of the test, the researchers relied on the logic and constructive validity indicators. Moreover, to estimate the reliability of the study, Cronbach Alpha was adopted. The study have concluded that there were no statistically significant differences between the male/female variable with respect to the cognitive motive.